Developmental changes of ketamine action against epileptic afterdischarges induced by hippocampal stimulation in rats - Mikolásová, R; Velísek, L; Vorlícek, J; Mares, P (Brain research. Developmental brain research, 1994)
Action of ketamine (5-40 mg/kg) was tested against electrically induced hippocampal afterdischarges (four stimulations in one session; 8 Hz, 15 s) in rats 7, 12, 18, 25 and 90 days old. In control sessions, there was either stable afterdischarge (AD) duration and wet dog shakes (WDS) number or there was an increase in ADs' duration with repeated stimulations. Ketamine had dose-dependent and age-dependent effects. In 7-18-day-old rats, ketamine suppressed better WDS number than AD duration, with nearly absent action on AD duration in 18-day-old animals. Ketamine was equipotent for both phenomena in 25-day-old rats and, in contrast, it decreased more AD duration than WDS number in 90-day-old rats. The data suggest a differentiation induced by ketamine in the expression of motor and electrographic phenomena of the experimental seizures.
Keywords: Animals; Ketamine; elektrická stimulace; Electric Stimulation; Epilepsy; vztah mezi dávkou a účinkem léčiva; hipokampus; Rats, Wistar; Age Factors; ketamin; Electrophysiology; Anticonvulsants; věkové faktory; chování zvířat; antikonvulziva; epilepsie; Dose-Response Relationship, Drug; Male; modely nemocí na zvířatech; Disease Models, Animal; krysa rodu Rattus; Behavior, Animal; elektrofyziologie; Hippocampus; zvířata; mužské pohlaví; elektroencefalografie; Rats; Electroencephalography; potkani Wistar